PENERAPANMETODE SURVEY QUESTION READ RECITED REVIEW (SQ3R) TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN SISWA PADA MATA PELAJARAN BAHASA INDONESIA KELAS III SDN 05 PEMUAR - Safarunita Wahyuni Reski; Mastiah Mastiah; Yumi Sarassanti (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2020)
Abstract:This study aims to determine differences in readingcomprehension skills in Indonesian subjects before and after using the Method Question Read Recited Review Survey (SQ3R) for students in the SDN 05 Pemuar. This research was conducted based on the background of the problem of teacher-centered learning processes, this is what makes students less active and look passive in the classroom, therefore students have difficulty absorbing the material and causing students' reading skills to understand the story text is less. Through this research the researcher hopes to be able to improve students' reading comprehension skills, especially in learning Indonesian in class III SDN 05 Pemuar. This research is an experimental study using thePretest-Posttest One-Group Design. The population in this study included all third gradestudents of SDN 05 PEMUAR with a sample of 14 people consisting of 9 male students and 5 female students. The sample used in this study is a saturated sample, therefore all members of the population are sampled. The preliminary data of this study usedavaluepretest with an average of 61.75 and an averagescore of posttest70.35.Based on the results of research tests of reading comprehension of students' understanding shows the value of t count of 49.571 and t table of 42.048 so that Ho is rejected and Ha is accepted because t count from t table. So it can be concludedthat with the Method it Question Read Recited Review Survey (SQ3R) has been proven effective against students' reading comprehension abilities, especially in class III SDN 05 Pemuar. Theresultsposttest show students' reading comprehension ability using the Survey Question Read Recited Review Method (SQ3R) higher than before being treated with the Method Question Read Recited Review Survey (SQ3R).Keywords: comprehension reading skills, Indonesian and Question Read Recited ReviewMethod(SQ3R). Abstrak:Penelitian ini bertujuan untuk mengetahuiperbedaankemampuanmembacapemahamanpada matapelajaran Bahasa Indonesiasebelum dan sesudahmenggunakan MetodeSurvey Question Read Recited Review (SQ3R) pada siswa SDN 05 PEMUAR. Penelitianinidilaksanakanberdasarkanlatarbelakangmasalah proses belajarberpusat pada guru, inilah yang membuatsiswakurangaktif dan terlihatpasif di dalamkelasmakadariitusiswakesulitanmenyerapmateri dan menyebabkankemampuanmembacasiswadalammemahamiteksceritakurang. Melaluipenelitianinipenelitiberharapmampumeningkatkankemampuanmembacapemahamansiswakhususnyadipembelajaran Bahasa Indonesia di kelas III SDN 05 Pemuar. Penelitianiniadalahpeneletianeksperimendengan menggunakan design One-Group Pretest-Posttest.Populasidalampenelitianinimencakupseluruhsiswakelas III SDN 05Pemuardenganjumlahsampel 14 orang yang tediridari 9 orang siswalaki-laki dan 5 orang siswaperempuan. Sampel yang dipakaidalampenelitianiniadalahsampeljenuh, makadariitusemuaanggotapopulasidijadikansampel. Data awalpenelitianinimenggunakannilaipretestdengan rata-rata 61,75 dan rata-rata nilaiposttest70,35.Berdasarkanhasilpenelitianteskemampuanmembacapemahamansiswamenunjukannilai t hitungsebesar 49,571 dan t tabelsebesar 42,048 sehingga Ho ditolak dan Ha diterimakarena t hitungdari t tabel. JadidapatdisimpulkanbahwadenganMetodeSurvey Question Read Recited Review (SQ3R) terbuktiefektifterhadapkemampuanmembacapemahamansiswakhususnya di kelas III SDN 05 Pemuar. Hasil posttestmenunjukankemampuanmembacapemahamansiswadenganmenggunakanMetodeSurvey Question Read Recited Review (SQ3R) lebihtinggidarisebelumdiberiperlakuandenganMetodeSurvey Question Read Recited Review (SQ3R). Kata Kunci: kemampuanmembacapemahaman, Bahasa Indonesia danMetodeSurvey Question Read Recited Review (SQ3R).